A Final Link From a Lost Arctic Expedition: A Letter by Sir John Franklin (1845) - Jin, Hanna; Bailey, Spenser (SourceLab, 2023)
Vol. 1, No. 3 (2019) With contributions by Bijan Mansoorieh This issue of SourceLab presents one of the last letters written by the Victorian explorer Sir John Franklin, who perished in the late 1840s while seeking the Northwest Passage. This publication is part of the digital documentary edition series SourceLab, based at the University of Illinois at Urbana-Champaign. Our Editorial Board conducts rigorous peer-review of every edition.